STOPP/START criteria for potentially inappropriate prescribing in older people: version 3 - O’Mahony, Denis; Cherubini, Antonio; Guiteras, Anna Renom; Denkinger, Michael; Beuscart, Jean-Baptiste; Onder, Graziano; Gudmundsson, Adalsteinn; Cruz-Jentoft, Alfonso J.; Knol, Wilma; Bahat, Gülistan; van der Velde, Nathalie; Petrovic, Mirko; et al. (European geriatric medicine, 2023)
Key summary points Aim To update and validate STOPP/START criteria for potentially inappropriate prescribing. Findings STOPP/START version 3 has been expanded and validated by an international European panel of experts in geriatric pharmacotherapy. Version 3, with 190 criteria, is significantly larger than version 2 (114 criteria), reflecting the expansion of the pharmacopeia and clinical trials evidence base relevant to older people since the publication of version 2. Message STOPP/START version 3 represents an updated explicit list of potentially inappropriate medications and potential prescribing omissions aimed at optimizing medication and minimizing adverse drug reactions and events during medication review in older people, particularly those with multimorbidity and polypharmacy. Purpose STOPP/START is a physiological systems-based explicit set of criteria that attempts to define the clinically important prescribing problems relating to potentially inappropriate medications (PIMs–STOPP criteria) and potential prescribing omissions (PPOs–START criteria). The previous two versions of STOPP/START criteria were published in 2008 and 2015. The present study describes the revised and updated third version of the criteria. Methods A detailed system-by-system review of the published literature from April 2014 to March 2022 was undertaken with the aim of including clinically important new explicit PIM and PPO criteria and removing any criteria considered to be no longer correct or outdated. A panel of 11 academic physicians with recognized expertise in geriatric pharmacotherapy from 8 European countries participated in a Delphi panel with the task of validating the draft criteria. The panel was presented with the draft new criteria using the SurveyMonkey® on-line platform in which panelists were asked to indicate their level of agreement on a five-point Likert scale. Results Two hundred and four evidence-based draft criteria (one hundred and forty-five STOPP criteria, fifty-nine START criteria) were presented to panelists for assessment using the Delphi validation method. Over the course of four rounds of Delphi validation, the panel achieved consensus on 133 STOPP criteria and 57 START criteria, i.e., 190 STOPP/START criteria in total representing a 66.7% increase in the number of criteria compared to STOPP/START version 2 published in 2015. Conclusion A fully revised and updated version of STOPP/START criteria has been validated by a European expert panel using the Delphi consensus process.